Early pregnancy maternal urinary metabolomic profile to predict fetal adiposity and macrosomia. (18th April 2012) - Walsh, JM; Wallace, M; Brennan, L; McAuliffe, FM
Abstract : Objective: Fetal macrosomia is associated with an increase in both adverse obstetric and neonatal outcome, and also confers a future risk of childhood obesity. The aim of this study was to determine if early pregnancy urinary metabolomic profiles could predict fetal adiposity and macrosomia. Study design: Fifty healthy secundigravid women who had previously delivered a macrosomic infant > 4kg were recruited. Fasting urine samples at 13.2±2.5 weeks were analysed using NMR spectroscopy and the spectra analysed using multivariate data analysis. Maternal glucose and insulin were measured in early pregnancy and at 28 weeks and the HOMA index calculated. At 34 weeks ultrasound assessed fetal anthropometry including anterior abdominal wall width (AAW), a marker of fetal adiposity. At delivery birthweight was recorded. Results: The median BMI of the study participants was 25.2kg/m2(22 – 30kg/m2). Principal component analysis was employed and a trend for separation of profiles according to birth weight was observed. Further to this probabilistic principal component with covariates analysis (PPCCA) of NMR metabolomic data was performed. Both fetal adiposity (AAW) and maternal insulin resistance at 28 weeks had a significant effect on the model. (AAW:95% CI: 0.66 to 3.93, p<0.05, HOMA: 95% CI: -4.91to-1.27, p<0.05). Conclusion: Our study, in a cohort of healthy women, has found that early pregnancy urinary metabolomic profile differs significantly according to fetal fat deposition in utero and maternal insulin resistance. These findings hold potential for early pregnancy identification of those at risk of both excessive growth in utero and impaired maternal glucose homeostasis.